2015
DOI: 10.1007/s11936-015-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysregulation as a Therapeutic Target for Acute HF

Abstract: Despite major advances that have led to effective therapeutic modalities for the treatment of heart failure (HF), this syndrome has continued to be a staggering health problem associated with significant mortality and morbidity. The increasing number of hospital admissions and readmissions related to acute HF continues to pose a fiscal challenge leading to constant interest in development of novel approaches. These point to multiple areas of unmet needs especially in acute HF, thus, necessitating further effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…An imbalance in the ANS is a predictor for a negative prognosis in patients with HF. It has been demonstrated that decreased vagal tone is associated with an increase in mortality for HF [ 28 ]. A recent report indicates that the neurotransmitter response of the cardiac vagal neurons in the brain stem is altered [ 29 ].…”
Section: Decreased Vagal Tone Is Associated With Increased Mortality mentioning
confidence: 99%
“…An imbalance in the ANS is a predictor for a negative prognosis in patients with HF. It has been demonstrated that decreased vagal tone is associated with an increase in mortality for HF [ 28 ]. A recent report indicates that the neurotransmitter response of the cardiac vagal neurons in the brain stem is altered [ 29 ].…”
Section: Decreased Vagal Tone Is Associated With Increased Mortality mentioning
confidence: 99%